1988
DOI: 10.1016/s0022-5347(17)42608-5
|View full text |Cite
|
Sign up to set email alerts
|

The Continent Ileal Bladder for Urinary Tract Reconstruction After Cystectomy: A Survey of 44 Patients

Abstract: The continent ileal bladder is an ileal pouch that is anastomosed to the urethral stump for urinary diversion after radical cystectomy. The ureters are implanted by an antireflux nipple ureteroileostomy. We report our results in 44 patients who underwent this type of diversion. The perioperative morbidity and mortality were comparable to those of an ileal conduit diversion. Urodynamic evaluation showed the ileal bladder to be a low pressure reservoir with a capacity that increased to more than 300 ml. The ilea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…Dur ing sleep, patients should have to awake to void once or twice [4], To overcome the deficits, Camcv modified his tech nique by the use of a detubularized ileal segment [2], The nighttime continence rate improved to 78% and 96% of the patients could stay dry in the daytime. Most patients achieved continence within 3-4 months following the operation [1,2], There are several methods of construction of the reser voir after detubularization of the ileum [ 1,[4][5][6]; however, there is no significant difference in the surgical morbidity, continence rate and urodynamic results among all these methods [1,2,[4][5][6][7], The patient's compliance and willing ness to become actively involved in the postoperative re education and training courses are even more important. A well-trained patient may void quite well in spite of a poor urodynamic result [4,7], In our study, the daytime continence rate (93%) is compatible with the data reported previously (table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dur ing sleep, patients should have to awake to void once or twice [4], To overcome the deficits, Camcv modified his tech nique by the use of a detubularized ileal segment [2], The nighttime continence rate improved to 78% and 96% of the patients could stay dry in the daytime. Most patients achieved continence within 3-4 months following the operation [1,2], There are several methods of construction of the reser voir after detubularization of the ileum [ 1,[4][5][6]; however, there is no significant difference in the surgical morbidity, continence rate and urodynamic results among all these methods [1,2,[4][5][6][7], The patient's compliance and willing ness to become actively involved in the postoperative re education and training courses are even more important. A well-trained patient may void quite well in spite of a poor urodynamic result [4,7], In our study, the daytime continence rate (93%) is compatible with the data reported previously (table 3).…”
Section: Discussionmentioning
confidence: 99%
“…[5] Melchior ct al. [6] After radical cystoprostatectomy, the proximal sphincteric unit of the bladder neck and the prostatic urethra are removed, the functional profile length is shortened. Also, the vesicourethral reflexes, which result in increased ure thral closure pressure wdth bladder filling, are lost [9], These phenomena may account for the loss of urinary continence after the operation.…”
mentioning
confidence: 99%
“…Urinary tract reconstruction following RC aims to provide an alternative to the native bladder. Improvements in bladder substitution techniques make it possible for a significant proportion of patients treated with RC to have an orthotopic bladder substitution as an alternative to ileal conduit (IC) [5][6][7] . Some groups advocate that orthotopic bladder substitution allows a quality of life (QoL) similar to that of individuals with a native bladder [8] .…”
Section: Introductionmentioning
confidence: 99%
“…The principal problems of artificial bladder replace ment are incontinence due to either insufficient sphincter tonus or involuntary contractions of the pouch [4,5], reflux of urine resulting in pyelonephritis [6], absorption KÄRGER © 1996 S. Karger AG, Basel 0042-1138/96/0564-0224S 10.00/0 E-Mail kargcr(fikargcr.ch F ax+ 41 61 306 12 34 of urinary solutes leading to metabolic complications [7][8][9][10], long-term complications due to the loss of 70 cm of ileum [11] and a possibly higher risk for the appearance of adenocarcinoma [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Special interest has focused on the problem of absorp tion of metabolites, since deaths due to hyperchloremic metabolic acidosis have been reported [6], The absorption of electrolytes has been studied extensively [7][8][9][10]. Ac cording to Koch et al [7], chloride, ammonium and potas sium are the principal ions reabsorbed by ileal segments, which can lead to hyperchloremic metabolic acidosis.…”
Section: Introductionmentioning
confidence: 99%